The role of xerophytic vegetation on fog harvest. (February 2023) - Cuevas, Jaime G.; Bustamante, Catalina; Ostria-Gallardo, Enrique; Hernández, Pedro
Abstract: Fog is an important resource for plant growth in arid communities. However, it is unclear whether small shrubs have an ability to capture fog water. We aimed to test this role and expected that were modulated by plant geometry (e.g., height, volume), as neighbor tree species do. Moreover, if xerophytes are adapted to this water resource, they should follow the temporal fluctuations in atmospheric fog offer, to exhibit a high efficiency in fog harvest, and capturing more fog than rain. Two sites in north-central Chile were worked, where 11–12 species per site were studied. Three funnels connected to bottles were placed beneath each plant, and evaluated monthly to quantify fog dripping. Fog offer was measured with standard fog collectors (SFCs). Several species collected more water than the controls in open spaces, reaching up to 182 mm/yr. A significant correlation of water harvest with plant height and volume was found. Only in the xeric site, water capture correlated significantly with SFC data. The capture efficiency was also the highest in this site. Fog harvest by plants was several times the rainwater input (31–34 mm), highlighting the role of xerophytes in the capture of the more abundant resource supplied by fog. Highlights: Xerophytic plants capture more fog than rain falling in fog ecosystems. Plant fog capture efficiency was higher in xeric than in mesic sites. The cactus Eulychnia breviflora had an annual efficiency of 73% in fog harvest. The most efficient species could be used as alternatives to artificial fog catchers.